Conceptualizing the Digital Sharing Economy in the Context of Sustainability - Maria J. Pouri (Sustainability, 2018)
Human society is increasingly influencing the planet and its environmental systems. The existing environmental problems indicate that current production and consumption patterns are not sustainable. Despite the remarkable opportunities brought about by Information and Communication Technology (ICT) to improve the resource efficiency of production and consumption processes, it seems that the overall trend is still not heading towards sustainability. By promoting the utilization of available and underused resources, the ICT-enabled sharing economy has transformed, and even in some cases disrupted, the prevailing patterns of production and consumption, raising questions about opportunities and risks of shared consumption modes for sustainability. The present article attempts to conceptualize the sustainability implications of today’s sharing economy. We begin with presenting a definition for the digital sharing economy that embraces the common features of its various forms. Based on our proposed definition, we discuss the theoretical and practical implications of the digital sharing economy as a use case of ICT. The analysis is deepened by applying the life-cycle/enabling/structural impacts model of ICT effects to this use case. As a result, we show the various positive and negative potentials of digital sharing for sustainability at different system levels. While it is too early to project well-founded scenarios to describe the sustainability status of digital sharing, the implications discussed in our work may help outlining future research and policies in this area.